Unlocking The Secret to Arabic Fluency: Exploring The Critical Role of Language Environment in Maximizing Arabic-Speaking Outcomes - Yul, Widiya; Rofingah, Umi; Andrian, Riko; Muhlasin, Muhlasin; Rozanie, Jihan Fitri (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2023)
Maximizing Arabic-speaking learning outcomes for MAN 1 Sungai Penuh students has been a significant goal. However, many students struggle to become proficient in the language despite this. This study aims to understand the underlying issues better. The research utilized a case study approach, incorporating interviews, observations, and documentation as data collection methods. Data reduction, display, and conclusion were employed as data analysis techniques. The results of this study indicate that the lack of a language-rich environment has hindered students' ability to develop Arabic speaking skills. The findings highlight the critical role of an immersive language environment in facilitating Arabic language learning. In conclusion, this research underscores the need for a language-rich environment for effective Arabic language learning. By providing an environment that encourages and supports Arabic language use, students at MAN 1 Sungai Penuh may be better equipped to acquire the language skills they need to succeed.